Pengolahan Sampah Styrofoam di Desa Wisata Sukunan Yogyakarta - Irfan Sakti Wahyu Prabowo; Dodit Ardiatma (Prosiding Sains dan Teknologi, 2022)
Styrofoam waste often causes problems in the environment because this material is difficult to undergo biological decomposition and is difficult to recycle so it is not in demand by scavengers. Besides having a negative effect on health, styrofoam is also not environmentally friendly, because it cannot be decomposed by nature, styrofoam will just accumulate and pollute the environment. Utilization of styrofoam waste has basically received attention for quite a long time, including making bricks from styrofoam with a very simple technique. In the manufacture of styrofoam gets a larger portion compared to other raw materials, explained as follows 50% styrofoam, 40% sand, and 10% cement. The use of styrofoam can save 50% of the need for sand compared to the use of bricks. Styrofoam raw material is also superior to cement because Styrofoam contains a lot of fiber. This makes the foundation of buildings that use Styrofoam stronger. Keywords: Styrofoam Waste, Styrofoam Bricks, Environmentally Friendly